MODEL PELAKSANAAN PRAKTIK KERJA INDUSTRI (PRAKERIN) KOMPETENSI KEAHLIAN TEKNIK PERMESINAN DI SMK NEGERI 1 KEDUNGWUNI - Wahyoto, Tutur (Journal of Mechanical Engineering Learning, 2014)
This study aims to describe the implementation of work practices in the industry SMK Negeri 1 Kedungwuni, cooperation with DU/DI and the dual system of education models used in prakerin. This research uses descriptive qualitative method. Research subjects Machinery Engineering class XII student, school as an organizer and DU/DI as a cooperation partner. Informants consisted of a tutor, Head of Engineering Machinery, students and DU/DI. Data collection techniques of observation, questionnaires, interviews and documentation. Results showed (1) prakerin implementation has been running very well, from the preparation stage prakerin, implementation and evaluation prakerin. Implementation prakerin by Machinery Engineering class XII students were divided into two waves. (2) collection of data through observation carried out in schools, a questionnaire was given to students of class XII Engineering Machinery, interview with the Head of Engineering Machinery, tutor, student and DU/DI. Documentation is done when the research is ongoing. The conclusions of this study: overview prakerin in SMK Negeri 1 Kedungwuni involves three stages: preparation prakerin aspects, implementation and evaluation prakerin. Model of the cooperation with DU/DI a MoU, a model release prakerin a block models for the students to concentrate on activities prakerin. Advice for schools to continue to maintain cooperation as well as possible because it has been running very well and prakerin value should be included in the certificate and the absence of a column value in the report cards.